Antioxidant, α-amylase and α-glucosidase Inhibitory Activities of Aqueous and Methanolic Extracts From Athamanta sicula L. - Loucif, Karima; Benchikh, Fatima; Souici, Chawki B.; Amira, Smain (Current Enzyme Inhibition, 2023)
Introduction: Oxidative stress plays a major role in developing diabetes complications; therefore, it is possible to use natural antioxidants as therapeutic agents for diabetes. Aims: This study aimed to find an important source of phenolics from Athamanta sicula L. (A. sicula) and confirm that this plant could be a significant source of medically important natural compounds by confirming its antioxidant, α-amylase and α-glucosidase inhibitory potential. Methods: Antioxidant property was performed using 2,2′-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, metal chelating, and cupric reducing antioxidant capacity methods. The α-amylase and α- glucosidase inhibitory activities were investigated using an in vitro model. Moreover, polyphenols and flavonoid contents of the tested extracts were carried out. Results: The methanolic extract exhibited the highest phenolic and flavonoid content compared to the aqueous extract. However, aqueous extract possessed the strongest antioxidant activity (DPPH scavenging, metal chelating, and Cupric ion reducing antioxidant capacities), α-amylase and α-glucosidase inhibitory effects. No correlation between phenolic content and antioxidant and enzyme inhibitory activities of A. sicula L. extracts was observed. Conclusion: The results showed that this plant could be a significant source of medically important natural compounds.
Keywords: antioxidant properties